Measurement of absolute branching fractions of D s + hadronic decays - Ablikim, M; Achasov, MN; Adlarson, P; Afedulidis, O; Ai, XC; Aliberti, R; Amoroso, A; An, Q; Bai, Y; Bakina, O; Balossino, I; Ban, Y; et al. (Springer, 2024)
Using e+e− collision data collected at the BESIII detector at center-of-mass energies between 4.128 and 4.226 GeV, corresponding to an integrated luminosity of 7.33 fb−1, we determine the absolute branching fractions of fifteen hadronic Ds+ decays with a double-tag technique. In particular, we make precise measurements of the branching fractions BDs+→K+K−π+=5.49±0.04±0.07%, BDs+→KS0K+=1.50±0.01±0.01% and BDs+→K+K−π+π0=5.50±0.05±0.11%, where the first uncertainties are statistical and the second ones are systematic. The CP asymmetries in these decays are also measured and all are found to be compatible with zero.